Can G-quadruplex become a promising target in HBV therapy? - Teng, Ye; Zhu, Ming; Chi, Yuan; Li, Lijing; Jin, Ye (Frontiers in Immunology, 2022)
The infection of chronic hepatitis B virus (HBV) is an important health problem that affect millions of people worldwide. Current therapies for HBV always suffer from the poor response rate, the common side effects and the need for lifelong treatment. Novel therapeutic targets are expected. Interestingly, non-canonical structures of nucleic acids play crucial roles in the regulation of gene expression. Especially the formation of G-quadruplexes (G4s) in G-rich strands have been demonstrated to affect many bioprocesses including replication, transcription and translation, showing great potential as the targets in anticancer and antiviral therapies. In this review, we summarized recent antiviral studies about G4s, and discussed the roles of G4 structures in antiviral therapy of HBV.